2022
DOI: 10.3389/fnut.2022.926814
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and functional changes of bioactive proteins in donor human milk treated by vat-pasteurization, retort sterilization, ultra-high-temperature sterilization, freeze-thawing and homogenization

Abstract: Background: Donor human milk should be processed to guarantee microbiological safety prior to infant feeding, but this process can influence the structure and quantity of functional proteins. Objective:The aim of this study was to determine the e ect of thawing, homogenization, vat-pasteurization (Vat-PT), retort sterilization (RTR) and ultra-high-temperature (UHT) processing on the structure of bioactive proteins in donor milk.Methods: Pooled donor milk was either not treated (Raw) or treated with an addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…30 In these cases, the Academy of Breastfeeding Medicine advises caretakers to discuss pasteurizing donor milk before consumption. 31 However, our data and and others 28 have shown that pasteurization significantly decreases the levels of osteopontin present in milk, which may compromise the biological activities of this protein.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…30 In these cases, the Academy of Breastfeeding Medicine advises caretakers to discuss pasteurizing donor milk before consumption. 31 However, our data and and others 28 have shown that pasteurization significantly decreases the levels of osteopontin present in milk, which may compromise the biological activities of this protein.…”
Section: Discussionmentioning
confidence: 49%
“…The copyright holder for this preprint this version posted February 26, 2023. ; https://doi.org/10.1101/2023.02.24.529945 doi: bioRxiv preprint pasteurization affect the levels of osteopontin in pooled donor breastmilk. 28 However, this report analyzed a single sample of previously-frozen pooled breastmilk, which may not fully represent the variance in other breastmilk sources. Thus, in this report, we investigated the levels of osteopontin in human breastmilk from different sources, and how pasteurization and freezing impact the concentration of this important bioactive component.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of pasteurization (Vat-PT, retort sterilization [RTR], or ultra-high-temperature [UHT] processing) as well as thawing and homogenization could influence the structure of bioactive proteins in DHM. 37 Overall, Vat-PT preserves more of bioactive proteins compared with UHT or RTR. 37 Similarly, traditional Holder pasteurization of DHM, while retaining the macronutrient concentrations, significantly reduces the bioactivity, including considerable loss of lysozyme and lactoferrin.…”
Section: Discussionmentioning
confidence: 94%
“… 37 Overall, Vat-PT preserves more of bioactive proteins compared with UHT or RTR. 37 Similarly, traditional Holder pasteurization of DHM, while retaining the macronutrient concentrations, significantly reduces the bioactivity, including considerable loss of lysozyme and lactoferrin. 38 Comparable to our observation, Akinbi et al and Chang et al reported preservation of bioactive protein in FroMOM compared with pasteurized DHM.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the difference in OPN levels reported between geographical sites [42] could partly be a consequence of the milk being collected at different times postpartum. Furthermore, the existence of geographical differences is questioned by studies reporting OPN levels of ~300-350 mg/L in milk from American mothers at undefined days postpartum [51] and 2-5 weeks postpartum [50]. These levels are comparable to the levels reported for Chinese mothers [42].…”
Section: Osteopontin In Human Milkmentioning
confidence: 97%